2016
DOI: 10.1002/clen.201400164
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Visible Light Active Ag‐ and N‐Doped KVMoO6: Photodegradation of Methylene Blue

Abstract: Brannerite-type layered vanadomolybdate, KVMoO 6 , was synthesized by sol-gel method using ethylene glycol as gelating agent. Its silver-and nitrogen-doped analogues were prepared by ion exchange and solid state methods, respectively. All compounds were characterized by powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), energy dispersive spectroscopy (EDS), Fourier transform IR spectroscopy (FT-IR), and UV-vis diffuse reflectance spectra. The bandgap energy of all compounds was obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The presence of Ag in the ANBT sample can be distinguished by two peaks centered at 367.2 eV and 373.4 eV, which are assigned to Ag 3d 3/2 and Ag 3d 5/2 , respectively (Figure e). These results confirm the presence of Ag + ion on the surface of ANBT . The Cu 2p spectrum displays Cu 2p 3/2 and Cu 2p 1/2 peaks centered at 934.4 and 954.6 eV, respectively, accompanied by two satellite signals at 943.6 and 963.2 eV, which corroborates the presence of Cu 2+ on the surface of CNBT (Figure f) , …”
Section: Resultssupporting
confidence: 77%
“…The presence of Ag in the ANBT sample can be distinguished by two peaks centered at 367.2 eV and 373.4 eV, which are assigned to Ag 3d 3/2 and Ag 3d 5/2 , respectively (Figure e). These results confirm the presence of Ag + ion on the surface of ANBT . The Cu 2p spectrum displays Cu 2p 3/2 and Cu 2p 1/2 peaks centered at 934.4 and 954.6 eV, respectively, accompanied by two satellite signals at 943.6 and 963.2 eV, which corroborates the presence of Cu 2+ on the surface of CNBT (Figure f) , …”
Section: Resultssupporting
confidence: 77%
“…The Ag 3d XPS spectrum of the Ag-KGTO sample exhibited the 3d 5/2 and 3d 3/2 peaks at 367.3 and 373.5 eV (Figure 4e), which are characteristics of Ag + ion. [48] As shown in Figure 4f, the Cu 2p XPS spectrum of the Cu-KGTO catalyst comprised 2p 3/2 and 2p 1/2 sublevels (at 934.4 and 954.7 eV, respectively) along with their corresponding satellites, which confirms the 2 + oxidation state of Cu. [49] The XPS spectrum of Sn 3d of Sn-KGTO is shown in Figure 4g.…”
Section: Characterization Studiesmentioning
confidence: 61%
“…Thus, it can be concluded that the Sn‐KGTO sample may exhibit higher photocatalytic activity originating from its highest surface adsorbed oxygen species. The Ag 3d XPS spectrum of the Ag‐KGTO sample exhibited the 3d 5/2 and 3d 3/2 peaks at 367.3 and 373.5 eV (Figure 4e), which are characteristics of Ag + ion [48] . As shown in Figure 4f, the Cu 2p XPS spectrum of the Cu‐KGTO catalyst comprised 2p 3/2 and 2p 1/2 sublevels (at 934.4 and 954.7 eV, respectively) along with their corresponding satellites, which confirms the 2+ oxidation state of Cu [49] .…”
Section: Resultsmentioning
confidence: 99%